You complete me: tumor cell-myeloid cell nuclear fusion as a facilitator of organ-specific metastasis - Cozzo, Alyssa J.; Coleman, Michael F.; Hursting, Stephen D. (Frontiers in Oncology, 2023)
Every cancer genome is unique, resulting in potentially near infinite cancer cell phenotypes and an inability to predict clinical outcomes in most cases. Despite this profound genomic heterogeneity, many cancer types and subtypes display a non-random distribution of metastasis to distant organs, a phenomenon known as organotropism. Proposed factors in metastatic organotropism include hematogenous versus lymphatic dissemination, the circulation pattern of the tissue of origin, tumor-intrinsic factors, compatibility with established organ-specific niches, long-range induction of premetastatic niche formation, and so-called “prometastatic niches” that facilitate successful colonization of the secondary site following extravasation. To successfully complete the steps required for distant metastasis, cancer cells must evade immunosurveillance and survive in multiple new and hostile environments. Despite substantial advances in our understanding of the biology underlying malignancy, many of the mechanisms used by cancer cells to survive the metastatic journey remain a mystery. This review synthesizes the rapidly growing body of literature demonstrating the relevance of an unusual cell type known as “fusion hybrid” cells to many of the hallmarks of cancer, including tumor heterogeneity, metastatic conversion, survival in circulation, and metastatic organotropism. Whereas the concept of fusion between tumor cells and blood cells was initially proposed over a century ago, only recently have technological advancements allowed for detection of cells containing components of both immune and neoplastic cells within primary and metastatic lesions as well as among circulating malignant cells. Specifically, heterotypic fusion of cancer cells with monocytes and macrophages results in a highly heterogeneous population of hybrid daughter cells with enhanced malignant potential. Proposed mechanisms behind these findings include rapid, massive genome rearrangement during nuclear fusion and/or acquisition of monocyte/macrophage features such as migratory and invasive capability, immune privilege, immune cell trafficking and homing, and others. Rapid acquisition of these cellular traits may increase the likelihood of both escape from the primary tumor site and extravasation of hybrid cells at a secondary location that is amenable to colonization by that particular hybrid phenotype, providing a partial explanation for the patterns observed in some cancers with regard to sites of distant metastases.